A CFD approach for numerical assessment of hydrodynamic coefficients of an inclined prism near the sea bottom. (15th May 2022) - Xiang, Gong; Guedes Soares, C.
Abstract: The hydrodynamic forces and dynamic responses of subsea structures, like manifolds, are studied in the final phase of their installation when they are near the sea bottom. The hydrodynamic coefficients of a submerged 3D prism are predicted through the constant acceleration method, which is implemented by the CFD tool OpenFOAM. In the constant acceleration method, the added mass force can be obtained at the moment that acceleration flow just begins or disappears by subtracting the drag force from the total hydrodynamic force. By comparing the CFD predictions with the corresponding available experimental and numerical results for the prism, a very good agreement indicates the validity of the proposed CFD method. The simulations of the flow past the prism with different inclined angles disclose the effect of the inclined angles on the hydrodynamic forces, pressure distributions, streamlines around the prism and finally the hydrodynamic coefficients. The bottom effect on the hydrodynamic coefficients of the prism is systematically studied through varying spacing ratios. At last, the inclined angle and spacing ratio are found to greatly affect the added mass coefficient and drag coefficient of the prism by changing the pressure distributions around it. The sensitivity of the hydrodynamic coefficients to the variation of the spacing ratio and inclined angles are studied and discussed. Highlights: The hydrodynamic forces and dynamic responses of manifolds, are studied in their installation when near the sea bottom. The hydrodynamic coefficients of a submerged 3D prism are predicted through the constant acceleration method. Comparing the CFD predictions with available experimental and numerical results, shows the validity of the method. The simulations of the flow past the prism with different angles disclose the effect of the angles on the hydrodynamic forces. The bottom effect on the hydrodynamic coefficients of the prism is systematically studied through varying spacing ratios.